Weed Management in Zimbabwean Smallholder Conservation Agriculture Farming Sector - Muoni , Tarirai; Mhlanga, Blessing (Asian Journal of Agriculture and Rural Development, 2014)
Weed management is one of the major constraints in the Zimbabwe smallholder farming sector contributing to smallholder poor yields, hence there is need to identify cropping systems that have potential to reduce weed pressure while improving crop yields. Conservation agriculture has been suggested as one of these farming systems. The implementation of CA three key principles reduces weed pressure even when the use of herbicides is minimised. Crops included in crop rotations, intercropping or relay cropping may have faster growth rate than weeds hence, have a comparative advantage over weeds. Maintenance of permanent soil cover through crop residues impedes weed germination thereby reducing weed population. Elimination of ploughing also reduces the chances of bringing buried weed seeds to the surface where their chances for germination are high. Hence, some seeds lose viability thus reducing weed density. Weed seeds accumulate at the surface, when allowed to set seed, increasing their exposure to predation resulting in reduction of weed density over time. The use of herbicides ensures that the fields are weed free as the season’s progress thus ensuring better yields at the end of each growing season. Hence, weeds are reduced in CA systems over time despite the weeding option used.